Tolosa hunt syndrome: case report of a 50-year-old man with unilateral headache ophtalmoplegia - Wardi, Baiq Prita Riantiani; Kholida, Baiq Hilya (Jurnal EduHealth, 2024)
Tolosa Hunt Syndrome (THS) is a rare clinical syndrome described as unilateral orbital or periorbital pain involving parese of one or more cranial nerves oculomotor (III), trochlear (IV), and or abducens (VI) caused by nonspecific granulomatous inflammation on the cavernous sinus, superior orbital fissure or orbital. MRI images can show thickening at cavernous sinus or orbital fissure. Giving corticosteroids for 48 hours resulted improvement in clinical symptoms. This article is a case report of a 50 years old man with Tolosa Hunt Syndrome. A 50-year-old man has come with complaints of recurrent headaches for 6 months in the left eye area, pain when moving his eyes, accompanied by burning sensation like electrocution, with difficulty moving the left eyeball to the left side and diplopia. Laboratory tests was normal, on MRI examination there is thickening of the musculus rectus lateralis. The patient was given injection methylprednisolone 125 mg/8 hours and gave good responses. Diagnosis of tolosa hunt syndrome (THS) in this case enforced based on the presence of unilateral headache in the periorbital area accompanied by weakness of the optic nerve (cranial nerves III and VI left), burning and electrifying feeling in the unilateral facial area indicating involvement of the nerve V1. Chronic inflammation of the cavernous sinus wall septa in dense connective tissue can exert pressure that can penetrate cranial nerves III, IV, VI and V branch 1. By giving of systemic corticosteroids for 48 hours resulted in improvement in clinical symptoms.